2013
DOI: 10.1136/bmjopen-2013-003185
|View full text |Cite
|
Sign up to set email alerts
|

European Public Assessment Report (EPAR) summaries for the public: are they fit for purpose? A user-testing study

Abstract: ObjectivesApply ‘user testing’ methodology to test the readability of a European Public Assessment Report (EPAR) summary—which describes how the decision was made by the European Medicines Agency to approve a medicine.DesignUser testing uses mixed methods (questionnaire and semistructured interview), applied iteratively, to assess document performance—can people find and understand key points of information.Setting and participantsTesting was undertaken with 40 members of the public in four consecutive rounds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 12 publications
(11 reference statements)
2
16
0
Order By: Relevance
“…Our results are concordant with other studies that have found a large degree of inconsistency in risk communication between healthcare professional and consumer audiences, both within and across countries . While other researchers considered the quantity or presence/absence of information overall and usefulness of information, this study is the first to our knowledge to focus on how professional and consumer labeling conveys risk information when the state of knowledge is incomplete, contradictory or inconclusive.…”
Section: Discussionsupporting
confidence: 91%
“…Our results are concordant with other studies that have found a large degree of inconsistency in risk communication between healthcare professional and consumer audiences, both within and across countries . While other researchers considered the quantity or presence/absence of information overall and usefulness of information, this study is the first to our knowledge to focus on how professional and consumer labeling conveys risk information when the state of knowledge is incomplete, contradictory or inconclusive.…”
Section: Discussionsupporting
confidence: 91%
“…Dosing instructions are provided by the prescriber, both verbally and written on a prescription. Written information is available in the package insert of the manufacturer and on the package itself (Raynor and Bryant, 2013;van Beusekom et al, 2016). Internationally, the package leaflet is the most common source of written information, with many studies covering this topic, and regulatory requirements concerning the content and comprehensibility of the text (Raynor and Bryant, 2013;Pires et al, 2016;Yuan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Written information is available in the package insert of the manufacturer and on the package itself (Raynor and Bryant, 2013;van Beusekom et al, 2016). Internationally, the package leaflet is the most common source of written information, with many studies covering this topic, and regulatory requirements concerning the content and comprehensibility of the text (Raynor and Bryant, 2013;Pires et al, 2016;Yuan et al, 2019). These requirements have been developed to ensure the information about medication on the outer package and the package leaflet is accessible, and written in plain language that can be understood by patients, including those with limited health literacy (European Commission, 2009a).…”
Section: Introductionmentioning
confidence: 99%
“…Principles of informed consent, informed and shared decision-making, and professional ethics all emphasize the importance of patients' understanding the potential harms and benefits of recommended therapies [2][3][4][5]. To help achieve this goal, many countries require that patients be given written medication information (WMI), usually in leaflet form, when they obtain a licensed medication [6][7][8]. However, patients often have difficulty understanding and using this information [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%